New mud turtles (Kinosternidae, Kinosternon) from the middle–late Miocene of the United States. (21st March 2016) - Bourque, Jason R.
Abstract: Kinosternon Spix, 1824, was widespread in xeric to savanna associated paleowetlands across North America during the middle–late Miocene and steadily diversified following its first occurrences in the Hemingfordian. In the middle Miocene, Kinosternon rincon n. sp. occurred in the late Barstovian Cerro Conejo Formation of north central New Mexico, perhaps concurrently with Kinosternon pojoaque Bourque2012a from the Tesuque Formation. Subsequent late Miocene kinosternine fossils indicate that at least three potentially contemporaneous species existed throughout the Clarendonian. These are Kinosternon pannekollops n. sp., from the Ogallala Formation of northern Texas; Kinosternon wakeeniense, n. sp., from the Ogallala Formation of northwestern Kansas and Ash Hollow Formation of south-central Nebraska; and Kinosternon notolophus n. sp., from the Alachua and Statenville formations of northern Florida. Kinosternon rincon is phylogenetically nested between the Kinosternon flavescens (Agassiz, 1857 ) group (= Platythyra Agassiz, 1857 ) and more derived Kinosternon including the Kinosternon subrubrum (Lacépède, 1788 ) group (= Thyrosternum Agassiz, 1857 ). Kinosternon pannekollops is recovered on the stem of the K . subrubrum group and is the oldest and largest member of that lineage. Kinosternon notolophus is readily differentiated from other Miocene Kinosternon in possessing a distinct dorsomedial keel on the nuchal and faint dorsolateral costal carination. The K . subrubrum group probably originated in the late Miocene savannas of the Great Plains and dispersed eastward via the Gulf Coastal Plain. An unnamed kinosternine taxon existed in the coastal plains of the eastern and southeastern United States during the Middle Miocene Climatic Optimum (with fossils from 18 to 15 Ma), and disappeared from the region coincident with the end of that megathermal event.